Elaboração e caracterização de queijo de leite de cabra tipo coalho com inclusão de leite de vaca - Santos, Barbara Melo (2011)
The use of new technologies for processing dairy goat s milk products can contribute to improving the agricultural livestock sectors of producing regions, particularly the microregions of Northeast Brazil. This research aimed to study the effect of the inclusion of bovine milk in the manufacturing of goat milk cheese curd to create a new marketable product. The study consisted of two experiments. In the first experiment, the milk products were prepared by varying the proportions of the milk mixture in five groups: Q1, goat milk; Q2, goat s milk and bovine milk at 3:1; Q3 goat s milk and bovine milk at 1:1; Q4 goat s milk and bovine milk at 1:3; and Q5 bovine milk. The completely randomized design consisted of three repetitions (tests) for these each of these five ratios at a fixed storage period (7 days of ripening). We performed microbiological (on both the raw material and cheese), colorimetric, melting, yield, composition (on both the raw material and cheese) and sensory analyses. In the second experiment, the cheeses were produced using three different formulations that varied the type of milk: BMQ, bovine milk; BGMQ bovine milk and goat s milk at 1:1; and GMQ, goat s milk. The completely randomized statistical design consisted of three repetitions (tests) for each of these three ratios and five different storage periods (1, 7, 14, 21 and 28 days). The type of milk used influenced (p<0.05) the following aspects of the physical and chemical composition: the level of fat and salt; the fatty acid content for C6, C8, C10, C12, C18:1n9c and C18:2n6c; the instrumental evaluation of the texture (only the hardness); and the predominance of parameters a* and b* in colorimetry. In tests of the sensory attributes, the odor of goat s milk and granularity of the cheese increased with a higher proportion of goat milk, and all the manufactured cheeses had mean scores better than the established standards in the acceptance test. This study shows how the quality and acceptability of the manufactured product develops or enhances beneficial substances. It thus adds value and contributes to the industry s growth by increasing the production of goat milk products.